2020
DOI: 10.1016/j.knee.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship of fixed vs mobile bearing unicompartmental knee replacement: A systematic review and meta-analysis of sixty-four studies and National Joint Registries

Abstract: This is a repository copy of Survivorship of fixed vs mobile bearing unicompartmental knee replacement: A systematic review and meta-analysis of sixty-four studies and National Joint Registries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…Thus, poor conformity and subsequent micro-motion in fixed implants may accelerate the development of AL (12). However, a recent meta-analysis by Abu Al-Rub et al which compared fixed with mobile bearing unicompartmental knee replacement did not find any difference between implant survivorship (46). A direct comparison of AL rates in cemented vs. uncemented UKAs were reported by Mohammad et al (33).…”
Section: Possible Explanation For Findingsmentioning
confidence: 99%
“…Thus, poor conformity and subsequent micro-motion in fixed implants may accelerate the development of AL (12). However, a recent meta-analysis by Abu Al-Rub et al which compared fixed with mobile bearing unicompartmental knee replacement did not find any difference between implant survivorship (46). A direct comparison of AL rates in cemented vs. uncemented UKAs were reported by Mohammad et al (33).…”
Section: Possible Explanation For Findingsmentioning
confidence: 99%
“…While many studies analyzed survivorship of FB-and MB-UKR and only reported second about functional outcome parameters, this present study focused primary on the clinical outcome of those designs [17,20,27,28]. Interestingly to date there are only 3 randomized control trials (RCT) comparing outcome parameters of both implant designs [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the revision rate of MB-UKR correlates more with surgical experience and usage of UKR [5,25,26]. In FB-UKR the most common modes of failure are polyethylene wear and progressive OA in late years [24,27]. Despite these differences in modes of failure and survivorship, a variety of studies suggesting similar functional outcomes between both designs [20,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile implants exhibit bearing dislocation as the main failure type [26]. Reports document that mobile UKA are more often revised for bearing dislocation comparing to fixed ones which are revised mainly for polyethylene wear [27]. Usually, bearing dislocations is documented to take place in the first post-operative 1 to 5 years [28] and is related to inaccurate ligament balancing or inappropriate bearing height [14].…”
Section: Atr-ftir Spectramentioning
confidence: 99%